Comparative efficacy of novel combination strategies for unresectable hepatocellular carcinoma: A network metanalysis of phase III trials. (October 2022) - Fulgenzi, Claudia A.M.; D'Alessio, Antonio; Airoldi, Chiara; Scotti, Lorenza; Demirtas, Coskun O.; Gennari, Alessandra; Cortellini, Alessio; Pinato, David J.
Abstract: Background: Dual programmed cell death-1 and vascular endothelial growth factor pathway inhibition is the novel standard of care for patients with unresectable hepatocellular carcinoma. Direct comparisons between first-line treatments are lacking. Method: We conducted a literature search in MEDLINE (https://pubmed.ncbi.nlm.nih.gov ), the Cochrane library (https://www.cochranelibrary.com ) and Embase (www.embase.com ) between January 2007 and February 2022. We included phase III randomised controlled trials that tested immune-checkpoint inhibitors or tyrosine kinase inhibitors, including sorafenib, lenvatinib and donafenib, and evaluated as primary end-point overall survival (OS) or progression-free survival (PFS). Studies testing loco-regional therapies were excluded. The primary end-point was to compare the efficacy of first-line options in terms of OS and PFS. We extracted Hazard ratios (HR) and 95% confidence intervals (95% CI) for OS and PFS and performed a frequentist network meta-analysis with fixed effect multivariable meta-regression models. The research protocol was registered in PROSPERO, an international prospective register of systematic reviews (registration code CRD42022312489). Findings: Literature review yielded 13709 results, after duplicates removal and exclusion of not relevant studies, 70 papers were available for screening. After full-text review, 9 studies were eligible for analysis. Atezolizumab plus bevacizumab reduced the risk of death compared to placebo (HR 0·40; 95% CI 0·28-0·57), sorafenib (HR 0·58; 95% CI 0·42-0·80), lenvatinib (HR 0·63; 95% CI 0·44-0·89), atezolizumab plus cabozantinib (HR 0·64; 95% CI 0·43-0·97), nivolumab (HR 0·68; 95% CI 0·48-0·98) and donafenib (HR 0·69; 95% CI 0·48-0·99). Atezolizumab plus bevacizumab was not statistically superior to durvalumab plus tremelimumab (HR 0·74; 95% CI 0·52-1·06) and sintilimab plus IBI305 (HR 1·02; 95% CI 0·67-1·55) in reducing the risk of death. Efficacy was associated with a higher risk of grade 3 adverse events. Highlights: Immune-checkpoint inhibitor plus anti-vascular endothelial growth factor agent provide the highest reduction in the risk of death in hepatocellular carcinoma. The efficacy of immune-checkpoint inhibitor plus anti-vascular endothelial growth factor is similar to that of dual checkpoint inhibition. The efficacy of combination strategies comes at the expense of higher toxicity. Nivolumab is associated with the lowest risk of adverse events.